The Influence of Bank Ownership on Bank Performance and Risks (The Case of Sharia Commercial Banks in Indonesia) - Ravindy, S; Laila, N; Nugraha Rani, L; Sucia Sukmaningrum, P (KnE Social Sciences, 2019)
This research aims to find out the influence of bank ownership (domestic, foreign, state-owned, or private) on bank performance and risks in Sharia Commercial Banks in Indonesia. This research uses quantitative approach with multiple linear regression analysis technique. The results of the research show that variable of Domestic-Foreign Bank has positive significant effects, variable of State Owned-Private Bank has negative not significant effects on the Return on Assets, and variable of Domestic-Foreign Bank has positive significant effects, variable of State Owned-Private Bank has negative significant effects to the Non-Performing Financing on Sharia Commercial Banks in Indonesia. Keywords: Ownership of Domestic-Foreign Bank, Ownership of State Owned-Private Bank, Return on Assets, Non-Performing Financing.